Experimentation in the works of the artist Muhammad Al-Kinani" an anaylytical study" (Al-Academy, 2022)
The problem of the tagged research (experimentation in the works of the artist Muhammad al-Kinani is an analytical study) dealt with the nature of the concept of experimentation and its work in the works of Muhammad al-Kinani. Which adopts the removal of the concept of style and artistic style and takes the experience away from the pattern of repetition The importance of the research comes through the identification of the materials founding the artistic work. The current research benefits the specialists in the field of arts from the students of studies with a new and renewed formulation of creativity. The research objectives shed light on the contemporary experiences of the artist Muhammad Al-Kinani and its importance in benefiting researchers and the specialized library, and the limits of the research were limited to Objective limits and temporal limits from 2006-2017 and spatial limits. As for the second chapter, represented by the theoretical framework, it contained three sections. The first topic dealt with the meaning of experimentation, the second topic was experimentation in the visual field, and the third topic dealt with experimentation in the works of the artist Muhammad Al-Kinani. The third chapter included the research procedures represented by the research community and the sample, which numbered (3) artistic works, then the research tools, the research method and the analysis of samples. As for the fourth chapter, it included the results and conclusions of the research, and the research reached a number of them.1- The artist’s interest in collage and pasting gypsum materials, cardboard and pastes.2- Re-formulation of the legacy in a new way, distinct and effective.As for the conclusions:1- The social, psychological and cultural conferences had a clear role in his experimental work.2- The artist was able to reflect his emotions through psychological and mythological values ​​to produce the artwork.3- Opening up to the outside world and benefiting from the experiences of others.As well as recommendations, suggestions and a list of sources